Development Of Soft Dough Biscuits With High Unsaturated Fatty Acids - Chandana, P.G.P.; Navaratne, S.B. (Journal of Multidisciplinary Engineering Science Studies (JMESS), 2015)
Attached
Keywords: Soft dough biscuits; Sunflower oil; Soybean oil; Com oil and Peanut oil; unsaturated fatty acids